Clinical applications and research progress of remifentanil - Xu Liu; Zhipeng Meng; Fei Tong (Frontiers in Anesthesiology)
IntroductionRemifentanil, an ultra-short-acting μ-opioid receptor agonist, is widely utilized in perioperative and critical care settings due to its rapid metabolism, predictable pharmacokinetics, and organ-independent clearance. This review synthesizes current evidence on its clinical applications, pharmacological advantages, and emerging challenges, including Opioid-Induced Hyperalgesia (OIH) and labor analgesia.MethodsThis study is a systematic evidence review. All data were derived from published literature, including retrospective studies by the authors' team. No new patient interventions or observational data were collected, consistent with ICMJE exemption criteria for secondary study types.ResultsPreclinical studies highlight molecular mechanisms of OIH involving microglial pathways (e.g., Nrf2-TRPV4 suppression, NF-κB/NLRP3 activation). Clinically, Remifentanil demonstrates significant efficacy in improving hemodynamic stability during extubation [reducing systolic blood pressure (SBP), diastolic blood pressure (DBP), and heart rate (HR) increases, P < 0.05], suppressing cough reflex in airway surgery (40–52% reduction, P < 0.05), and accelerating recovery [reduced extubation/post-anesthesia care unit (PACU) times by 18.3%/22.1%, P < 0.01]. It exhibits synergistic effects with dexmedetomidine for blood pressure control in specific scenarios (P < 0.05) and protects against sufentanil-induced coughing (OR = 0.42). However, OIH risk is dose-dependent (>0.2 μg/kg/min, OR = 2.1, P < 0.05), and its antitussive efficacy and hemodynamic impact vary significantly by surgical context (P = 0.01) and BMI (P = 0.004). Compared to epidural analgesia, Remifentanil for labor shortens duration (mean -1.8 hours) and reduces intervention rates (cesarean relative risk (RR) = 0.78, instrumental RR = 0.62) but carries a higher risk of maternal respiratory depression (OR = 3.92). In ICU, it does not significantly shorten mechanical ventilation duration compared to other opioids (P > 0.05).DiscussionRemifentanil offers significant advantages in perioperative hemodynamic control and recovery acceleration. Key challenges include managing OIH risk, contextual variability in efficacy (surgery type, BMI), and safety considerations in special populations (neonates, severe obesity) where long-term data are limited. Translational gaps persist between preclinical OIH mechanisms and clinical precision medicine strategies. Future research should prioritize multicenter trials to validate dosing protocols [especially lean body mass (LBM)-adjusted in obesity], biomarker-driven approaches for OIH mitigation, and long-term neurodevelopmental safety assessments.